Training of Trainers (ToT) on Enhancing National Climate Services (ENACTS) Maprooms for Users in Zambia - Grossi, Amanda; Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A five-day training of trainers (ToT) workshop was implemented from November 7 to November 11, 2022, in Lusaka, Zambia by the International Research Institute for Climate and Society (IRI) in collaboration with the Zambia Meteorological Department (ZMD) and the International Water Management Institute (IWMI). The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 18 participants from the Zambia Meteorological Department (ZMD) alongside the Zambia Agriculture Research Institute (ZARI), the Ministry of Green Economy and Environment (MGEE), the Water Resources Management Authority (WARMA), the Ministry of Agriculture (MoA), the International Water Management Institute (IWMI), and the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) to be trained on ZMD’s existing suite of free online ENACTS Maprooms. The major objective of the workshop was to ensure that each of these institutions that play an important role in promoting the use of climate information and services and broader resilience of the agricultural sector are aware of and have the capacity to train users within Zambia on the best-available climate information products for decision-making. The ENACTS maproom products, which are freely available through ZMD’s website, provide location-specific (4 km grid) historical, monitoring, and forecast information that is important for activities related to planning, monitoring, and response for the agricultural sector and wider food system.